(untitled) (Web of Teachers: Inderscience Research, 2024)
A comparative analysis of the prospects of creating ultra - thin, light and highly efficient solar cells based on AlGaAs/GaAs heterostructures was conducted. Technological challenges and prospects for each option are discussed. A micron - scale thinning of AlGaAs/GaAs heterostructures using efficient technological methods has been proposed, which has been shown to significantly increase the yield percentage of solar cells.